Asymmetric effects of public debt on economic growth: Evidence from emerging and frontier SADC economies - Bongumusa Prince Makhoba; Irrshad Kaseeram; Lorraine Greyling (Cogent Economics & Finance, 2022)
This study interrogates asymmetric effect of public debt on economic growth among selected emerging and frontier SADC economies. The study estimates a smooth transition regression (STAR) to analyse asymmetric relationship between public debt and economic growth using time series data from 2000 to 2018, extracted from the World Development Indicators. The findings indicate a strong evidence of a significant asymmetric relationship between public debt and growth among emerging and frontier SADC members under consideration. The results revealed the inverted U-Shape effect of public debt on growth in South Africa. While the results for Botswana, Namibia, Zambia and Zimbabwe indicate that there is a U-Shape relationship between public debt and economic growth. The study suggest that policymakers ought to consider curbing public debt level within a sustainable threshold target in order to reduce accompanying debt serving costs, and efficiently use public finances consistent with sustainable economic expansion.
Keywords: 330; Public debt; Economic growth; Smooth Transition Regression; SADC